Fixed-time traffic signal optimization procedures for undersaturated and oversaturated conditions. - Cronjé, Wilhelm Blomerus (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil.)-University of Stellenbosch, 1985.